Evolution And Contribution Of Artificial Intelligencess In Indonesian Education - Rahula Hananuraga; Nasril Nasril; Agustinus Tanggu Daga; Opan Arifudin; Petrus Jacob Pattiasina (Journal of International Multidisciplinary Research, 2025)
The aim of this research is to analyze the evolution and contribution of artificial intelligence (AI) in the Indonesian education system. This research aims to understand how AI technology has developed and been applied in various aspects of education, from administration, personalized learning, to evaluating learning outcomes. The research methods used are literature studies and secondary data analysis from various sources, including academic journals, government reports, and case studies of AI implementation in a number of educational institutions in Indonesia. The research results show that AI has made a significant contribution to improving administrative efficiency, facilitating more adaptive learning, and providing in-depth data analysis for educational decision making. However, challenges such as the digital divide, limited infrastructure, and the need to increase teacher competency in using AI technology still need to be overcome. This research concludes that with the right policy support and investment in infrastructure and training, AI has great potential to transform Indonesian education in a more inclusive and quality direction.